Analysis of Tourism Potential of The Kalimosodo River in The Effort of Improving The Economic Welfare of The Community in Sudimoro Village - Azizah, Ika Nur; Susilo, Agus (Proceedings International Conference on Education Innovation and Social Science, 2022)
Research on the potential analysis of Kalimosodo River Tourism in an effort to improve the economic welfare of the community in Sudimoro Village aims to find out how the efforts to develop the potential that exist in Sudimoro Village, to determine community involvement in tourism management in Sudimoro Village, and to determine the economic welfare of the community in the environment around tourism, seen from the increase in people's income before and after the tourism. The research method used is a qualitative method. Data collection techniques using observation, interviews and documentation. The results of this study indicate that (1) the efforts made in developing the potential are through the APBDes which is then budgeted for the manufacture of tourism supporting facilities (2) the community is involved in tourism development, decision making, and trade (3) with this tourism opening opportunities especially for the people of Sudimoro Village, so that they can increase their income.